Graphene field emission devices - DUESBERG, GEORG (My University, 2014)
Graphene field emission devices are fabricated using a scalable process. The field enhancement factors, determined from the Fowler-Nordheim plots, are within few hundreds and match the theoretical predictions. The devices show high emission current density of ∼10 nA μm−1 at modest voltages of tens of volts. The emission is stable with time and repeatable over long term, whereas the noise in the emission current is comparable to that from individual carbon nanotubes emitting under similar conditions. We demonstrate a power law dependence of emission current on pressure which can be utilized for sensing. The excellent characteristics and relative ease of making the devices promise their great potential for sensing and electronic applications.
PUBLISHED
Keywords: Carbon nanotubes; Electrodes; Current density; Field emission; Graphene